2022
DOI: 10.3174/ajnr.a7544
|View full text |Cite
|
Sign up to set email alerts
|

Navigating Supply Chain Disruptions of Iodinated Contrast Agent for Neuroimaging and How Business Intelligence Can Help the Decision Process

Abstract: A recent coronavirus disease 2019-related shutdown of the main production facility of iohexol in China has led to massive shortages of iodinated contrast material across the globe. This shortage has also jeopardized neuroimaging. In this article, we describe remedies to reduce iodinated contrast material use for stroke imaging, which is its primary use in neuroimaging, that we have implemented in our hospital network.ABBREVIATIONS: BI ¼ Business Intelligence; CE ¼ contrast-enhanced; coronavirus disease ¼ COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…In addition to the strategies proposed by the previously stated agencies, clinicians at hospital systems globally have described their experiences and plans for managing ICM shortages, including those reported by institutions in Australia, 4,20,31,32 Germany, 33 and the US. 1,5,7,16,17,19,[34][35][36][37][38]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the strategies proposed by the previously stated agencies, clinicians at hospital systems globally have described their experiences and plans for managing ICM shortages, including those reported by institutions in Australia, 4,20,31,32 Germany, 33 and the US. 1,5,7,16,17,19,[34][35][36][37][38]…”
Section: Resultsmentioning
confidence: 99%
“…For example, clinicians in the US and Australia determined contrast-enhanced CT was commonly used for abdominopelvic indications, for which alternative options (including CT without contrast) are available. 32,55 The American College of Radiology's ACR appropriateness criteria provides guidance on alternative imaging modalities. 56…”
Section: Improve Communication Via Command Centresmentioning
confidence: 99%
“…A staged response was adopted, drawing upon guidance that has been issued by professional bodies, including the American College of Radiology (ACR), and various authors from affected institutions. 2,[4][5][6][7][8][9] GE has reported that its factory in Shanghai has recommenced operations, with production expected to normalize in mid-June. 2 While we have started receiving some new inventory in Australia, the lag-effects of the shortage, uncertainty associated with the pandemic, disruption of supply chains, reactive 'panic' buying across the globe, and lack of transparency regarding production mean that the imbalance between supply and demand may well last longer than anticipated.…”
Section: Introductionmentioning
confidence: 99%
“…Many radiology departments and practices therefore introduced strategies to reduce ICM consumption, in order to conserve inventory for those critical CTs and procedures which are necessary to prevent death or significant morbidity. A staged response was adopted, drawing upon guidance that has been issued by professional bodies, including the American College of Radiology (ACR), and various authors from affected institutions 2,4–9 …”
Section: Introductionmentioning
confidence: 99%
“…3 In response, strategic health departments and medical imaging providers have been required to rapidly assess their current contrast usages and implement strategies to conserve limited supplies for most time critical indications, such as stroke presentations and acute lower gastrointestinal bleeding. 4,5 The American College of Radiology (ACR) Committee on Drugs and Contrast Media has recently issued guidance on conserving ICM during the supply shortage, with their recommendations largely endorsed by the Royal Australian and New Zealand College of Radiologists (RANZCR). 6,7 These strategies include utilising alternative imaging modalities to answer clinical questions, weight-based contrast dosing and lower kVp CT protocols to improve the conspicuity of ICM.…”
Section: Introductionmentioning
confidence: 99%